The Impact of the Study of the Social Situation in the Realization of Al-Sharia Provisions’ Matters and Connecting them with Muklafin: An Applied Fundamentalist Study - AL-Shroosh, Ahmad (Dirasat: Shari’a and Law Sciences, 2023)
Objectives: The study aims to show the importance of studying the social status of the responsible ones for achieving the main concerns of judgments, as a stage of achieving the special concerns, and to show its impact on the implementation of judgments on the responsible ones. Methods: The study followed the analytical approach by clarifying the relationship between the conditions of the responsible people and achieving the concerns of judgments. The study also adopted the applied-rooting approach by showing the impact of the case study of the responsible ones in achieving the concerns of those entitled to Zakat and estimating marital alimony. Results: This research found that studying the social status of the responsible people is a stage of achieving the concerns of provisions, and studying the social status of them strengthens the preponderance of the belief of the Mujtahid (the one who is responsible for issuing rules) of the validity of applying provisions correctly. The study also revealed that provisions of responsible ones change in accordance with the change in their conditions and interests. Conclusions: The study concludes that considering the social status of the responsible one achieves the purpose of the legislation, and strengthens the preponderance of belief in the validity of the achievement of the concerns of justice and applying it to the responsible ones. The study recommends that the judge will not be satisfied with looking at the surface of the situation without taking the social situation into account. It also recommends conducting studies on the impact of the conditions of the responsible people in the field of worship, transactions, and Sharia politics.